Credit Market Imperfection and Sectoral Asymmetry of Chinese Business Cycle - Zhang, Yuanyan (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes the role of credit market imperfection and sectoral asymmetry as a means through which shocks to the real economy are propagated and amplified. Drawing on firm-level data to calibrate the model, our simulations capture two key stylized facts of the Chinese economy: that credit constraints are more binding in nontradable sectors than in tradable industries and that output volatility is much greater in China than in industrial economies. We find that the driving force behind our simulation results is strongly related to the non-uniform nature of credit market imperfections in China and their implications for resource allocation and the way in which the economy reacts to shocks. Correctly capturing these macro-financial interactions are essential to understand the dynamic behavior of the Chinese economy.